Special Dietary Habits for Pubertal Women: A Study Based on Ikkirigollewa Muslim Village - Aroosiya Banu, M.S. (South Eastern University of Sri Lanka, 2024)
Purpose: The main objective of the present study is to emphasize the significance of special food consumption by pubescent to the Muslim community. Methodology: The study was carried out in a group of 60 females aged between 10 to 14 years. The primary and secondary data obtained from the study are analyzed through quantitative and qualitative data analysis methods. Finding: Kurakkan flour puttu, Rice flour puttu, Ulzuthankazli, Country chicken egg, Brinjal juice, Brinjal milk curry, Beef curry, Country chicken curry, liver, and sesame oil are given to the respective participants of the study. Being Muslim village, the study area serves largely non vegetarian meals during the puberty. As per the present study, grinding cooking method is decreased and normal cooking method is increased among the Muslim community of Ikirigollewa village. During puberty most of the participants offer to take raw chicken eggs which lead to biotin deficiency. Eating habits of adolescents are determined by various socio- cultural factors. Implication: The finding provides insights to help special food consumption by pubescent to the Muslim community to healthy conception and delivery. Theoretical Contribution: The finding will lead to new changes and knowledge among Muslims regarding special diets followed during puberty. Limitation: No research regarding this title and lack of cooperation of participant are the limitation of this study. Originality: This study is significant because it hasn't been conducted by any researchers
Keywords: Puberty; Adolescence; Special foods; Nutrition